Progression of Pulmonary Emphysema and Continued Increase in Ectodomain Shedding of Cell Adhesion Molecule 1 After Cessation of Cigarette Smoke Exposure in Mice - Ri, Aritoshi; Hagiyama, Man; Inoue, Takao; Yoneshige, Azusa; Kimura, Ryuichiro; Murakami, Yoshinori; Ito, Akihiko (Frontiers in Cell and Developmental Biology, 2018)
Pulmonary emphysema usually arises in cigarette smokers, and often progresses after smoking cessation and even in ex-smokers. Lung-epithelial cell adhesion molecule 1 (CADM1), an immunoglobulin superfamily member, is extracellularly shed to produce a proapoptotic C-terminal fragment (CTF) within the cell and contribute to the development of emphysema. Here, we made an ex-smoker model using C57BL/6 mice; mice (6-week-old; 5 mice per group) were exposed to passive smoke of eight cigarettes twice a day 5 days a week until 18 weeks of age, and were then left untreated until 30 weeks of age. We calculated the mean linear intercept (Lm) and the alveolar septal thickness in the lung histologic sections to estimate the alveolar space dilatation. At 18 weeks of age, Lm was marginally enlarged (P = 0.023) with a marked increase in the septal thickness (P < 0.001) in comparison with age-matched control mice (5 mice per group), while at 30 weeks, the increase in Lm was much more prominent (P = 0.006) and the septal thickness was normalized, suggesting that emphysema progressed with septal remodeling during smoking cessation. Western blot analyses of the lungs were performed for CADM1, a possible CADM1 sheddase ADAM10, an epithelial marker pan-cytokeratin, and a myofibroblastic marker α-smooth muscle actin to estimate the expression levels of CTF and ADAM10 per epithelial cell and the levels of pan-cytokeratin and αSMA per tissue. CADM1 shedding was increased in the treated mice than in control mice at both ages, in association with an increase in the CTF level at 30 weeks (P = 0.021). In total of the treated and control mice of 30 weeks of age, Lm was positively correlated with the CTF and ADAM10 levels, and pan-cytokeratin was negatively correlated with CTF, suggesting an involvement of CADM1 shedding in emphysema progression. Positive correlations were also found between CTF and ADAM10, and between ADAM10 and αSMA, suggesting that increased septal myofibroblasts might be involved in increased CADM1 shedding. Taken together, persisting increase in ectodomain shedding of CADM1 appeared to contribute to the progression of emphysema in ex-smokers, and might be accounted for by alveolar septal remodeling.